1999
DOI: 10.1016/s0006-3495(99)77463-1
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Pipette Interactions Underlie Delayed Voltage Activation of Mechanosensitive Channels in Xenopus Oocytes

Abstract: To investigate the mechanism for the delayed activation by voltage of the predominant mechanosensitive (MS) channel in Xenopus oocytes, currents were recorded from on-cell and excised patches of membrane with the patch clamp technique and from intact oocytes with the two-electrode voltage clamp technique. MS channels could be activated by stretch in inside-out, on-cell, and outside-out patch configurations, using pipettes formed of either borosilicate or soft glass. In inside-out patches formed with borosilica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
(62 reference statements)
1
15
0
Order By: Relevance
“…While these pressures are larger than reported elsewhere [1], they are consistent with our previous reports [2]. We believe the lower pressures required by other labs are related to differences in the glass or saline compositions used that can affect the resting tension in the patch dome and the patch mechanical properties during stimulation [35], [51].…”
Section: Resultssupporting
confidence: 90%
“…While these pressures are larger than reported elsewhere [1], they are consistent with our previous reports [2]. We believe the lower pressures required by other labs are related to differences in the glass or saline compositions used that can affect the resting tension in the patch dome and the patch mechanical properties during stimulation [35], [51].…”
Section: Resultssupporting
confidence: 90%
“…Gil et al (10) hypothesize that voltage across the patch influences membrane tension and gates SA channels. Because depolarization activation did not occur with soft glass pipettes and was absent in outside-out patches, they concluded that voltage dependence was an artifact resulting from specific interactions between the glass pipette and membrane patch in Xenopus oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used for single-channel recording from patches of membrane from oocytes obtained from Xenopus laevis have been described (6,7). The neurons used for recording were cultured from the hippocampal region of embryonic (e15) rat brain as described (20).…”
Section: Methodsmentioning
confidence: 99%
“…Two different experimental approaches were used to test whether preventing movement of the membrane also prevented activation of MS channels. The first approach was based on an observation made in a previous study: depolarization-induced delayed activation of MS channels no longer occurs when the tips of the borosilicate glass pipettes are coated with soft glass (7). Perhaps this lack of activation with soft glass arose from a lack of movement of the membrane patch, because soft glass has a different composition and charge density that may interact with the membrane differently than hard glass (24).…”
Section: Depolarization-induced Membrane Displacement and Ms Channelmentioning
confidence: 99%
See 1 more Smart Citation